Preparation and Characterization of Edible Films Made from Modified Sweet Potato Starch through Heat Moisture Treatment - Novita Indrianti; Yudi Pranoto; Akmadi Abbas (Universitas Gadjah Mada, 2018)
The edible films were prepared from native sweet potato starch (SPS) or modified sweet potato starch through heat-moisture treatment (HMT). The treatments which were carried out in this research were the different durations of HMT (1, 2, and 3 h) and the SPS concentrations (1, 1.25 and 1.5%). The edible films were characterized by moisture content, thickness, tensile strength, elongation, water vapor permeability (WVP), solubility, morphology, thermal, and x-ray diffraction. The result showed that the thickness, the tensile strength, and the elongation of the modified SPS edible films were higher while the WVP and the solubility were lower than those of the native SPS edible films. The longer durations of HMT had no effects on the characteristics of the edible films. The increase of SPS concentrations enhanced the moisture content, the thickness, the WVP and the elongation but decreased the solubility and the tensile strength of edible films. The films surfaces of modified SPS edible films appeared to be denser and compact than those of native SPS edible films. The crystallinity and the thermal properties of the modified SPS edible films showed the higher increase than those of the native SPS edible films.